2010
DOI: 10.1007/s11237-010-9153-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-chemical DFT calculations of the energies of the O—H bond of phenols

Abstract: The energies of homolytic cleavage of the O-H bonds in 36 phenols with various structures were calculated within the scope of density functional theory using a series of exchange-correlation functionals and basis sets. The best agreement between the calculated and experimental data is given by the M06-2X/6-311++G(2d,2p)Phenols are widely used in technology and medicine as antioxidants. Their arsenal in this respect is quite extensive and continues to grow at a fast pace both on account of artificially synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…62 As described in the in silico section above, since the established computational models KPS-1 and KPS-2, as the core layers of energy within hydrogen-bonding aggregates, are prevalent in the corresponding crystal structures and play dominant roles in intermolecular interactions, KPS-1 and KPS-2 were selected as the subjects of comparative studies to comprehensively understand the fluctuations in the local polarity after FCY cocrystallized with VAA. To this end, the MEP calculations were performed using the B3LYP(D3) method with the 6-311G(d,p) basis set, 38 and the gained MEP maps plotted by the VMD software are shown in Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…62 As described in the in silico section above, since the established computational models KPS-1 and KPS-2, as the core layers of energy within hydrogen-bonding aggregates, are prevalent in the corresponding crystal structures and play dominant roles in intermolecular interactions, KPS-1 and KPS-2 were selected as the subjects of comparative studies to comprehensively understand the fluctuations in the local polarity after FCY cocrystallized with VAA. To this end, the MEP calculations were performed using the B3LYP(D3) method with the 6-311G(d,p) basis set, 38 and the gained MEP maps plotted by the VMD software are shown in Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
“…37 The B3LYP-D3/6-311G(d,p) level was used for the computation of the molecular electrostatic potential (MEP) and reduced density gradient (RDG), and displayed by the VMD software. 38,39 All the wave function analyses were executed using the Multiwfn 3.8 program. 40 Single-crystal X-ray diffraction (SCXRD) testing.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that M06-2X is one of the best DFT functionals for BDE calculations with satisfactory accuracy. By using this functional, the mean absolute deviations between the experimental and calculated values are 6.5 and 2.0 kJ mol –1 for absolute and relative BDEs, respectively. , The BDEs in this study were calculated as follows where E (Ph), E (R), and E (H) represent the energies of phenolic compounds and the radicals R and H , respectively. ZPE­(Ph) and ZPE­(R) represent the corresponding zero-point energies.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…By using this functional, the mean absolute deviations between the experimental and calculated values are 6.5 and 2.0 kJ mol −1 for absolute and relative BDEs, respectively. 44,45 The BDEs in this study were calculated as follows…”
Section: ■ Introductionmentioning
confidence: 99%